Safety evaluation of unsignalized and signalized restricted crossing U-turn (RCUT) intersections in rural and suburban areas based on prior control type. (July 2022) - Mishra, Raunak; Pulugurtha, Srinivas S.
Abstract: The focus of this paper is on evaluating the safety effectiveness of restricted crossing U-turn (RCUT) intersections in rural and suburban areas based on prior control type. Both, unsignalized and signalized RCUT intersections were evaluated using the Empirical Bayes (EB) before-after evaluation method. The 42 RCUT intersections selected for this research were converted from a two-way stop-controlled (TWSC) intersection or signalized intersection in the rural and suburban areas. The results show a 70.63% reduction in the total number of crashes and a 76.10% reduction in the number of fatal and injury crashes at unsignalized stop-controlled RCUT intersections in the rural area. Also, an 89.25% reduction in the total number of crashes and a 94.42% reduction in the number of fatal and injury crashes was observed at offset three-legged unsignalized stop-controlled RCUT intersections converted from four-legged TWSC intersections in rural areas. In the suburban areas, a 64.86% reduction in the total number of crashes and a 73.39% reduction in the number of fatal and injury crashes was observed at unsignalized stop-controlled RCUT intersections. Further, a 10.15% and a 31.08% reduction in the total number of crashes, and an 84.26% and 41.31% reduction in the number of fatal and injury crashes was observed at a signalized RCUT intersection in the rural and suburban areas, respectively. The safety effectiveness of unsignalized RCUT intersections in the rural areas with a larger sample size was found to be higher than was observed by researchers in the past. While unsignalized RCUT intersections in the suburban areas are effective, there is not enough evidence to support the installation of signalized RCUT intersections. These findings help researchers and practitioners in making informed decisions and installing RCUT intersections from a safety perspective. Highlights: A significant reduction in the total number of crashes after RCUT intersections are installed. Effective at 41 out of the 42 selected RCUT intersections. Level of effectiveness differs for RCUT intersections in rural and suburban areas. Level of effectiveness differs for RCUT intersections with unsignalized and signalized U-turn median openings.